Study of surface integrity and dimensional accuracy in EDM using Fuzzy TOPSIS and sensitivity analysis - Dewangan, S. (Elsevier B.V., 2015)
Surface integrity and dimensional accuracy remain critical concern in Electrical Discharge Machining (EDM). The current research work aims at investigating the influence of various EDM process parameters like pulse current (Ip), pulse-on time (Ton), tool work time (Tw) and tool lift time (Tup) on various aspects of surface integrity like white layer thickness (WLT), surface crack density (SCD) and surface roughness (SR). The dimensional accuracy, characterized by over cut (OC), has also been studied in the similar way. A response surface methodology (RSM) - based design of experiment has been considered for this purpose. The present study also recommends an optimal setting of EDM process parameters with an aim to improve surface integrity aspects after EDM of AISI P20 tool steel. This has been achieved by simultaneous optimization of multiple attributes (i.e. WLT, SCD, SR and OC) using Fuzzy-TOPSIS-based multi-criteria decision making (MCDM) approach. The optimal solution was obtained based on five decision makers' preferences on the four responses (i.e. WLT, SCD, SR, and OC). From this analysis, an optimal condition of process parameters of Ip = 1 A, Ton = 10 Î¼s, Tw = 0.2 s, and Tup = 1.5 s has been determined. Furthermore, sensitivity analysis was also carried out to study the sensitivity or robustness of five decision makers' preference of optimal machining parameters. Form this study, decision makers' preference for surface crack density has been found to be the most sensitive response and therefore should be chosen first and analyzed very carefully. Â© 2014 Elsevier Ltd. All rights reserved.